2018
DOI: 10.1016/j.diabres.2018.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between periodontitis and development of diabetes

Abstract: There is no association between periodontitis and risk of prediabetes/diabetes in this longitudinal study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 37 publications
2
53
0
2
Order By: Relevance
“…Several important works not included in our study were worth reading. Chiu's study [62] and Joshipura's study [74] found PD could increase the risk of developing pre-diabetes. Demmer's study [75] found PD was associated with 5-year HbA1c progression.…”
Section: Discussionmentioning
confidence: 95%
“…Several important works not included in our study were worth reading. Chiu's study [62] and Joshipura's study [74] found PD could increase the risk of developing pre-diabetes. Demmer's study [75] found PD was associated with 5-year HbA1c progression.…”
Section: Discussionmentioning
confidence: 95%
“…Several important works, though notable, were not included in our study. Chiu's study [62] and Joshipura's study [74] found that periodontitis could increase the risk of developing prediabetes. Demmer's study [75] found that periodontitis was associated with 5-year HbA1c progression.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between diabetes and periodontitis is bidirectional, with each conferring a higher risk of the other (18,19). Epidemiologic studies have confirmed that diabetes is an important risk factor for periodontitis, and it has been recognized that periodontitis is the sixth-most frequent complication of diabetes (20). The incidence rate of periodontitis in diabetics is obviously higher.…”
Section: Clinical and Epidemiologic Characteristics Of Oral Bone Metamentioning
confidence: 99%